Energy and nutrient consumption in Mexican women 12-49 years of age: analysis of the National Nutrition Survey 1999 Consumo de energía y nutrimentos en mujeres mexicanas de entre 12 a 49 años de edad: análisis de la Encuesta Nacional de Nutrición 1999 - Simón Barquera; Juan A Rivera; Juan Espinosa-Montero; Margarita Safdie; Fabricio Campirano; Eric A Monterrubio (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To describe the reported energy and nutrient intake and adequacies in Mexican women. MATERIAL AND METHODS: A 24-hour dietary recall was used to obtain nutrient intake in a representative sub-sample of 2 630 women from 12 to 49 years of age from the National Nutrition Survey 1999. Nutrient adequacies were estimated using the Dietary Reference Intakes and stratified according to region, area (urban or rural), socioeconomic status and obesity status (non-obese: BMI <30 kg/m², obese: >30 kg/m²). Differences were analyzed using linear regression for complex surveys of log-transformed intake and adequacy, adjusting for multiple comparisons with the Bonferroni test. RESULTS: The median national energy intake was 1 471 kcal. The Risk of Inadequacy (RI) (prevalence of adequacy <50%) was: vitamin A:38.3%, vitamin C: 45.5%, and folate: 34.3%. Carbohydrates, folate, iron and calcium intake was significantly higher in rural than in urban areas. The RI was higher in women of the lowest socioeconomic status tertile for all nutrients with the exception of carbohydrates and calcium. Macro-nutrient adequacies were significantly higher in non-obese women. CONCLUSIONS: Differences within the country among regions, rural and urban areas, and socioeconomic status tertile reflect an increasing availability of inexpensive calorie-dense foods in marginal groups. However, total energy, cholesterol, saturated and total fat were consumed in greater quantities by women from the higher socioeconomic status tertile and from urban areas. These patterns could be a contributing factor to the rise of obesity and other non-communicable nutrition-related chronic diseases in Mexico. OBJETIVO: Describir la ingesta reportada de energía y nutrimentos en mujeres mexicanas. MATERIAL Y MÉTODOS: Se utilizó un recordatorio de 24 horas para obtener la ingesta de energía en una submuestra representativa de 2 630 mujeres de 12 a 49 años de edad de la Encuesta Nacional de Nutrición 1999. Las adecuaciones nutrimentales se estimaron utilizando las Referencias de Ingesta Dietética y fueron estratificadas por región, área urbana o rural, nivel socioeconómico y presencia de obesidad (no-obesas: IMC <30 kg/m², obesas: >30 kg/m²). Las diferencias se analizaron utilizando modelos de regresión lineal para encuestas complejas del logaritmo de la ingesta y la adecuación, ajustando para comparaciones múltiples con la prueba de Bonferroni. RESULTADOS: La media nacional de ingesta de energía fue de 1 471 kcal. El riesgo de inadecuación (prevalencia de adecuación <50%) fue vitamina A: 38.3%, vitamina C: 45.5% y folato: 34.3%. La ingesta de carbohidratos, folato, hierro y calcio fue significativamente más alta en áreas rurales que en las urbanas. El riesgo de inadecuación fue mayor en mujeres del nivel socioeconómico más bajo para todos los nutrimentos con excepción de carbohidratos y calcio. Las adecuaciones de macro-nutrimentos fueron significativamente mayores en mujeres no-obesas. CONCLUSIONES: Las diferencias entre las regiones, áreas del país y terciles de nivel socioeconómico reflejan una disponibilidad creciente de alimentos densamente calóricos de bajo costo en grupos marginales. Sin embargo, la energía total, colesterol y la grasa saturada y total se consumieron en mayores cantidades por mujeres del tercil de nivel socioeconómico más alto y áreas urbanas. Estos patrones pueden estar contribuyendo al incremento de la obesidad y otras enfermedades no transmisibles en México.